2015
DOI: 10.1007/s00436-015-4746-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of Toxoplasma gondii infection in stray dogs in northern China

Abstract: Toxoplasma gondii is a zoonotic protozoan of almost all species of mammals and birds. However, no information is available about seroprevalence of the pathogen in stray dogs in seven cities from Inner Mongolia, Jilin, Liaoning province, China. Using the indirect hemagglutination antibody (IHA) test with a cutoff titer of 1:64, 129 (14.05 %) out of 918 stray dogs were surveyed to be T. gondii seropositive. Analysis of the risk factor showed that there was no statistical difference of seroprevalence of T. gondii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It may cause asymptomatic infection or severe symptomatic infection including developmental defects, early embryonic death, stillbirth, or abortion to T. gondii-infected pregnancies (Dubey and Jones, 2008;Dubey and Dubey, 2010;Pan et al, 2017). Dogs are the intermediate hosts, and multiple studies have demonstrated the prevalence of T. gondii in dogs in a variety of countries or areas worldwide (Jiang et al, 2015;Zhang et al, 2015;Dubey et al, 2016;Rengifo-Herrera et al, 2017;Zarra-Nezhad et al, 2017). Although these serological surveys and diagnosis analysis of dogs infected T. gondii have been reported, the interactions between the host dog and the parasite T. gondii remain not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It may cause asymptomatic infection or severe symptomatic infection including developmental defects, early embryonic death, stillbirth, or abortion to T. gondii-infected pregnancies (Dubey and Jones, 2008;Dubey and Dubey, 2010;Pan et al, 2017). Dogs are the intermediate hosts, and multiple studies have demonstrated the prevalence of T. gondii in dogs in a variety of countries or areas worldwide (Jiang et al, 2015;Zhang et al, 2015;Dubey et al, 2016;Rengifo-Herrera et al, 2017;Zarra-Nezhad et al, 2017). Although these serological surveys and diagnosis analysis of dogs infected T. gondii have been reported, the interactions between the host dog and the parasite T. gondii remain not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasmosis is a zoonosis caused by T. gondii (Zhang et al 2015). It is widely parasitic in human and animal nucleated cells (Kang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that one-third of the human population is infected by the parasite. The majority of infections are asymptomatic; however, T. gondii infection in pregnant women and immunocompromised patients can cause serious illnesses and even death (ZHANG et al, 2015). Similarly, infection in dogs may be asymptomatic, but clinical signs are variable and may include respiratory, digestive, ocular, and neuromuscular symptoms (HOSSEININEJAD et al, 2011;LANGONI et al, 2013).…”
Section: Introductionmentioning
confidence: 99%